2021
DOI: 10.3390/ijms22052258
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell-Based Therapies and Glioblastoma Management: Current Evidence and Clinical Challenges

Abstract: Gliomas, which account for nearly a quarter of all primary CNS tumors, present significant contemporary therapeutic challenges, particularly the highest-grade variant (glioblastoma multiforme), which has an especially poor prognosis. These difficulties are due to the tumor's aggressiveness and the adverse effects of radio/chemotherapy on the brain. Stem cell therapy is an exciting area of research being explored for several medical issues. Neural stem cells, normally present in the subventricular zone and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 109 publications
(135 reference statements)
0
34
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) are multipotent progenitor cells that can be isolated from several tissues, including bone marrow (BM), adipose tissue, umbilical cord (UC), and placenta, because of their anti-inflammatory, anti-apoptotic and immunomodulatory properties. MSCs have been used in clinical trials for various disorders, including NDDs [199,200]. In addition, EXOs derived from MSCs have been considered effective for treating various pathological conditions, including CNS disorder, and their ability to rescue dopaminergic neurons in neurotoxic synthetic organic compound 6-hydroxydopamine (6-OHDA) mice models of PD.…”
Section: Stem Cells-derived Exosmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent progenitor cells that can be isolated from several tissues, including bone marrow (BM), adipose tissue, umbilical cord (UC), and placenta, because of their anti-inflammatory, anti-apoptotic and immunomodulatory properties. MSCs have been used in clinical trials for various disorders, including NDDs [199,200]. In addition, EXOs derived from MSCs have been considered effective for treating various pathological conditions, including CNS disorder, and their ability to rescue dopaminergic neurons in neurotoxic synthetic organic compound 6-hydroxydopamine (6-OHDA) mice models of PD.…”
Section: Stem Cells-derived Exosmentioning
confidence: 99%
“…These findings demonstrated the feasibility and efficacy of using an NSC-based delivery system. It is noteworthy that researchers have observed a close contact (possibly physical) between NSCs and glioma cells through the use of immunohistochemistry and fluorescence immunohistochemistry (107)(108)(109)(110)(111). More importantly, Benmelouka et al (108) observed that the transplanted NSCs were capable of differentiating into neurons, astrocytes and oligodendrocytes in vivo.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…It is noteworthy that researchers have observed a close contact (possibly physical) between NSCs and glioma cells through the use of immunohistochemistry and fluorescence immunohistochemistry (107)(108)(109)(110)(111). More importantly, Benmelouka et al (108) observed that the transplanted NSCs were capable of differentiating into neurons, astrocytes and oligodendrocytes in vivo. Therefore, NSCs may incorporate into the neuron-glioma circuit or neuron-glial network and form NGSs between neurons and gliomas.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…Gliomas, which consist of a group of heterogeneous brain tumors originating from three types of glial cells, namely astrocytes, oligodendrocytes, and ependymal cells, account for almost 80% of primary malignant brain tumors in adults [1][2][3][4][5][6]. The incidence and mortality rate associated with gliomas are expected to increase dramatically in the upcoming years, particularly in developing countries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to unfavorable pharmacokinetics of chemotherapeutic drugs, poor drug delivery across the blood-brain barrier (BBB) and blood-tumor barrier (BTB) prevents them from exerting their therapeutic action properly. The inherent chemoresistance of the brain endothelium and glioma cells, expressing the drug efflux protein p-glycoprotein also impairs the therapeutic efficacy [2,3]. Moreover, clinical applications are limited by adverse effects, such as bone marrow suppression, genotoxic, and teratogenic effects [10].…”
Section: Introductionmentioning
confidence: 99%